Laboratory Examination in Hemophagocytic Lymphohistiocytosis - Wulyansari Wulyansari; Yetti Hernaningsih (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Hemophagocytic Lymphohistiocytosis (HLH) is derived from the word hemophagocytosis, in which macrophages infiltrate tissue extensively, and unspecifically phagocyte blood and bone marrow cells. The deviant activation of cytotoxic CD8+ T-cells causing the release of inflammatory cytokines is the core pathogenesis of HLH. Hemophagocytic lymphohistiocytosis is a regulatory disorder of the immune system, with clinical signs and symptoms of extreme inflammation and cytopenia, hepatitis, and severe and life-threatening central nervous system dysfunction. The name of the HLH disorder was recently proposed to be "Hyperinflammatory Lymphohistiocytosis" (also known as HLH). Enforcement of HLH diagnosis by the Histiocyte Society based on HLH 2004 updated diagnostic criteria consists of five of the following eight diagnostic criteria: fever, splenomegaly, cytopenia (two or more of three lineages in peripheral blood), hypertriglyceridemia or hypofibrinogenemia, hyperferritinemia, hemophagocytes in the bone marrow/lien/lymph, the low or non-existent activity of Natural Killer (NK) cells, increased sCD25. H-score, MH-score, and systemic Juvenile Idiopathic Arthritis (sJIA)/Macrophage Activated Syndrome (MAS) classification criteria are also used to enforce HLH diagnoses. Hemophagocytic lymphohistiocytosis is challenging to recognize and has a high mortality rate, especially in adults, ranging from 42 to 88%. Therefore, immediate diagnosis and therapy are essential. The introduction of HLH triggers is critical because treatment is based on the underlying trigger. Cytokine storms due to Coronavirus Disease 19 (COVID-19) infection have significant similarities to the clinical and laboratory findings of HLH. Secondary HLH (sHLH) is suspected in severe COVID-19 patients, so early diagnosis is potentially made based on the H-score.